COMPARATIVE ANALYSIS OF SUSTAINABILITY STUDIES CONDUCTED IN HIGHER EDUCATION INSTITUTIONS IN TURKEY - Demirtaş, Sefa; Özcan, Ahmet (Bursa Teknik Üniversitesi, 2025)
Sustainability is a critical concept that has been considered important by humanity, especially in the last fifty years. The uncontrolled increase in production activities brought about by the Industrial Revolution has caused limited natural resources to start to deplete rapidly and the ecosystem to be destroyed. This problem, which has been known for decades, has not been sufficiently taken into consideration by the world public. However, the destruction in question has reached critical levels in recent years, making it necessary for humanity to focus on sustainability. In the presented study, the sustainability activities of higher education institutions as non-profit organizations were examined in Turkey. The focus was on the top 10 universities from Turkey that were successful in entering the UI Green Metric list published in December 2024, and the correlation between the performances of these universities in the sustainability index and their performances in Times Higher Education (THE), where academic success is more prominent, was examined. According to the findings obtained for the universities examined, a significant correlation was found between THE and UI Green Metric performances.

Sürdürülebilirlik, özellikle son elli yıldır insanoğlu tarafından önemsenen oldukça kritik bir kavramdır. Sanayi Devriminin getirmiş olduğu üretim faaliyetlerinin kontrolsüz şekilde artması, kısıtlı doğal kaynakların hızla tükenme eğilimine girmesine ve ekosistemin tahrip olmasına sebep olmuştur. Onlarca yıldır bilinen bu sorun dünya kamuoyu tarafından yeterince dikkate alınmamış olmasına rağmen özellikle son dönemlerde bahsi geçen tahribatın kritik boyutlara ulaşması insanlığın sürdürülebilirlik üzerine eğilmesini zorunlu hale getirmiştir. Sunulan çalışmada, kâr amacı gütmeyen kuruluşlar olarak yükseköğretim kuruluşlarının sürdürülebilirlik faaliyetleri Türkiye özelinde incelenmiştir. 2024 yılı Aralık ayında yayınlanan UI Yeşil Metrik (Green Metric) listesine Türkiye’den girme başarısını gösteren ilk 10 üniversiteye yoğunlaşılmış ve söz konusu üniversitelerin sürdürülebilirlik endeksindeki performansları ile akademik başarının daha ön plana çıktığı Times Higher Education (THE) performansları arasındaki korelasyon incelenmiştir. İncelenen üniversiteler özelinde elde edilen bulgulara göre THE ile UI Yeşil Metrik performansları arasında anlamlı bir korelasyon olduğu tespit edilmiştir.
Türkiye’deki Yükseköğretim Kurumlarında Yapılan Sürdürülebilirlik Çalışmalarının Karşılaştırmalı Analizi
Keywords: International Relations (Other); Uluslararası İlişkiler (Diğer)